2024
DOI: 10.1101/2024.01.18.576250
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of the potential food allergy risks of recombinant human lactoferrin expressed inKomagataella phaffii

Yanisa Anaya,
Raysa Rosario Martinez,
Richard E. Goodman
et al.

Abstract: Prior to the introduction of novel food ingredients into the food supply, safety risk assessments are required, and numerous prediction models have been developed and validated to evaluate safety. The allergenic risk potential of Helaina recombinant human lactoferrin (rhLF, Effera™), produced inKomagataella phaffii(K. phaffii) was assessed by literature search, bioinformatics sequence comparisons to known allergens, glycan allergenicity assessment, and a simulated pepsin digestion model. The literature search … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…However, the extent and type of N-glycosylation have a profound impact on the therapeutic properties of many proteins [167][168][169]. Studies have successfully demonstrated a glycoengineering strategy in K. phaffii that enables the production of completely humanized and immunologically compatible recombinant lactoferrin, although with considerably lower yields (Table 2) [133,170]. It is well established that glycosylation of human lactoferrin occurs predominantly at three sites: Asn-156, Asn-497, and Asn-642 [167].…”
Section: Milk Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the extent and type of N-glycosylation have a profound impact on the therapeutic properties of many proteins [167][168][169]. Studies have successfully demonstrated a glycoengineering strategy in K. phaffii that enables the production of completely humanized and immunologically compatible recombinant lactoferrin, although with considerably lower yields (Table 2) [133,170]. It is well established that glycosylation of human lactoferrin occurs predominantly at three sites: Asn-156, Asn-497, and Asn-642 [167].…”
Section: Milk Proteinsmentioning
confidence: 99%
“…It is well established that glycosylation of human lactoferrin occurs predominantly at three sites: Asn-156, Asn-497, and Asn-642 [167]. The process to produce humanized lactoferrin involves eliminating endogenous yeast glycosylation pathways, such as some glycosyltransferases, followed by the gradual introduction of heterologous glycosylation enzymes, including mannosidases, other glycosyltransferases, and epimerases [168,170]. This approach contributes to increasing the half-life of the glycoprotein in vivo and eliminates allergenic potential, thus enhancing the therapeutic value of yeast-derived glycoproteins [171].…”
Section: Milk Proteinsmentioning
confidence: 99%
“…The use of hmLF isolated from human milk has not been pursued due to economic, ethical, and sustainability reasons. Approximately one liter of human milk is required to yield 100 mg of hmLF 17 ; not only is this practice costly and wasteful, but milk used for this purpose could be unsuitable for feeding infants. The expression of recombinant proteins provides a method for production at commercial scale with prospective sustainability benefits, and at a lower cost and without ethical concerns.…”
Section: Introductionmentioning
confidence: 99%
“…The use of hmLF isolated from human milk has not been pursued due to economic, ethical, and sustainability reasons. Approximately one liter of human milk is required to yield 100 mg of hmLF; 20 not only is this practice costly and wasteful, but milk used for this purpose could be unsuitable for feeding infants. The expression of recombinant proteins provides a method for production at commercial scale with prospective sustainability benefits, and at a lower cost and without ethical concerns.…”
Section: Introductionmentioning
confidence: 99%